2020
DOI: 10.1002/jlb.5a0820-436r
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of human neutrophil phenotypes as biomarker to monitor exercise-induced immune changes

Abstract: The amplitude of the innate immune response reflects the degree of physiological stress imposed by exercise load. An optimal balance of exercise intensity and duration is essential for a balanced immune system and reduces the risk of dysfunction of the immune system. Therefore, it is hypothesized that neutrophils, as key players in the innate immune system, can be used as biomarker in detecting overtraining. The aim was to monitor the state of the innate immune system by phenotyping neutrophils during consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 40 publications
(97 reference statements)
2
14
0
Order By: Relevance
“…It could be that some of the data we have shown are affected by difference in age between the study groups. However, we have investigated similar neutrophil activation markers in previous studies and found no difference in baseline expression levels between ages 59 . Furthermore, we state that there is no neutrophil activation in COVID‐19 patients at presentation.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…It could be that some of the data we have shown are affected by difference in age between the study groups. However, we have investigated similar neutrophil activation markers in previous studies and found no difference in baseline expression levels between ages 59 . Furthermore, we state that there is no neutrophil activation in COVID‐19 patients at presentation.…”
Section: Discussionsupporting
confidence: 56%
“…Because the healthy controls are relatively young compared to the patients included in this study, it is important to emphasize that the expression of nCD10/neprilysin on neutrophils measured by automated flow cytometry is not dependent on the age of the donor. 28,59 Expression of CD10/neprilysin is high as seen in neutrophils in healthy control blood (Fig. 7E and Marini et al 54 ).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Additionally, athletes have large inter-individual CK response dierences to the same exercise, further complicating the analysis of CK levels for recovery status [93]. Other biomarkers, which can be analysed for exercise recovery include transforming growth factor beta 1 (TGF-ÎČ1) [408], oxylipin [744], brain-derived neurotrophic factor (BNDF), oxygen reduction potential (ORP, redox potential) [647], cell-free DNA (cfDNA) [60], and neutrophil phenotypes [762].…”
Section: G Brain Imagingmentioning
confidence: 99%